Rehabilitation training inhibits neuronal apoptosis by down-regulation of TLR4/MyD88 signaling pathway in mice with cerebral ischemic stroke - Sun, Yan (Am J Transl Res, 2021)
Objective: To investigate the role of rehabilitation training and TLR4/MyD88 signaling pathway on neuronal apoptosis in mice with cerebral ischemic stroke. Methods: Mice were randomized into six groups, which were normal group (healthy mice, n=20), control group (sham surgery, n=20), model group (middle cerebral artery occlusion (MCAO) model, n=20), training (MCAO model, continuous rehabilitation training for 4 weeks, n=20), TAK-242 group (MCAO model, TL R4 inhibitor TAK-242, n=20), and TAK-242 + Training group (MCAO model, TLR4 inhibitor TAK-242 + rehabilitation training, n=20). Results: Neurobehavioral assessment was performed, and cerebral infarction area of mice was detected by triphenyl tetrazolium chloride staining. Compared with the normal group, no significant differences in all indicators were found in the control group (all P>0.05), while the other groups had higher neurological function scores, cerebral infarction area, neuronal apoptosis rate, increased expressions of TLR4, MyD88, Bax, NF-κB, TNF-α, Caspase-3, IL-1βA and decreased mRNA and protein expressions of Bcl-2 (all P<0.05). Conclusion: Rehabilitation training can effectively reduce the apoptosis of hippocampal neurons in mice with ischemic stroke by inhibiting the TLR4/MyD88 signaling pathway.